Simulation of damage scenarios in a FRP composite suspension footbridge - Wahab, M. Abdel; Votsis, Renos; Chryssanthopoulos, M. K. (My University, 2005)
Simulations of damage scenarios were carried out using a finite element model of a newly constructed FRP composite footbridge, the Wilcott footbridge. This footbridge represents a new generation of suspension footbridges that have lightweight decks made of pultruded glass fibre reinforced polymer (GFRP) composite elements. It offers several advantages over conventional steel or concrete footbridges, e.g. speed of installation, high resistance to corrosion and saving in weight and foundations. On the other hand, its lightness and slenderness make it more sensitive to dynamic effects, both at serviceability and ultimate limit states. A finite element model using 3-D beam elements was constructed and damage scenarios were simulated and introduced in the model. The natural frequencies, mode shapes as well as time responses due to pedestrian loading were predicted. Different size of delamination in the composite deck was simulated at various locations along the bridge. The sensitivity of natural frequencies and mode shapes due to delamination were assessed by comparing the results of the damaged deck to those of the reference intact deck. The effect of changes in the cables' initial strains on the modal parameters was also examined, and the sensitivity of modal parameters to cable degradation was assessed.
Keywords: Damage; Finite elements; FRP composites; Suspension footbridge